Continuation Study of the Response of Subterranean Termites (Coptotermes formosanus )to Organosilane Treated Wood Wafers (Isoptera: Rhinotermitidae) - Johnson, Todd E. (Sociobiology, 2014)
A standard laboratory termite test was conducted in May of 2012 using termites from a single colony of Coptotermes formosanus (Shiraki) gathered in South Central Mississippi. Testing was performed adhering to procedures outlined in the AWPA E1-09 Standard termite test. Wood wafers used in the test were treated with an organosilane compound that has been shown to cause color changes and erratic behavior in native termite species ( Johnson & others 2011). Significant results were obtained on the weight loss of treated wafers as well as termite mortality. Observations of worker termites exposed to treated wood wafers during testing did not reveal any abnormal termite activity, and no significant post mortem observations were made, as were made with Reticulitermes sp. It is hypothesized that the pathogenic response of the gut bacteria Serratia marcescens (Bizio) in Reticulitermes sp.to the organosilane compound was not observed in C. formosanus due to a higher resistance to immuno threats.